Mineralogical and geochemical aspects of sand dunes in Missan Governorate, Southeastern Iraq - Al-Halfi, Fadia Waleed; Al-Khafaji, Sattar Jabbar (Iraqi Journal of Science, 2022)
Twenty sand samples were collected from the sand dunes of Missan fields, Southeastern Iraq. Grain size distribution, mineralogical and chemical composition were studied for the total, medium, and fine-size sand fractions. The grain size analysis shows that the sand is the main component, followed by silt and trace of clay. The predominant grain size of sand is 0.250 to 0.500 mm, which forms more than 57.28 %, which indicates that these dunes were formed under the influence of relatively strong winds and the sedimentary material is close to the source. The light components are quartz, feldspar, and different rock fragments, while the heavy mineral assemblages are composed of opaque minerals, chlorite, mica, and amphiboles. Pyroxene and epidote are the common minerals, while zircon, garnet, tourmaline, rutile, kyanite, and staurolite are in minor amounts. X-ray diffraction (XRD) data reveals that the predominant non-clay minerals are quartz, calcite, feldspar, and gypsum. While the dominant clay minerals are palygorskite and illite, followed by kaolinite and the mixed layer of montmorillonite – chlorite. There is a negative relationship between the percentage of heavy minerals and the grain size of sand. Dunes are distinguished by a relatively high percentage of minerals derived from intermediate and basic igneous rocks located in the Zagros belt, northern Iraq. They also may be derived from local source formations, Injana and Mukdadiya in the surrounding areas. The average geochemical components of sand as indicated by X-ray fluorescence (XRF) are; SiO2 (61.36%), which is mainly represented by quartz, CaO (14.08%) related to the presence of carbonate, SO3 (0.05%) is represented by gypsum, Al2O3 (6.76 %) and alkalis (2.30%) reflect the presence of the K-feldspar and clay minerals, Fe2O3 (3.2%) is attributed to the presence of hematite, magnetite and limonite minerals. SiO2 is concentrated in a medium sand size fraction, while the other oxides are concentrated in a fine sand size fraction.